Changes in offender-rated working alliance in probation supervision as predictors of recidivism - Sturm, Annelies (Psychology, crime & law, 2021)
Although the association between working alliance and outcome is a consistent finding in voluntary psychotherapy research, there is a lack of knowledge of the significance of this concept in mandated treatment. This study examined the relationship between the offender-rated working alliance and recidivism in a sample of 199 offenders mandated to community supervision. Working alliance was disentangled in trait-like and state-like components. Cox regression analysis was used. The working alliance subscales were measured by the Working Alliance with Mandated Clients Inventory (WAMCI). When controlling for crime history or risk level, the state-like change patterns of the working alliance subscale Trust predicted general and serious recidivism during the four year follow-up period. When controlling for crime history, the trait-like early alliance subscales Trust and Reactance predicted serious recidivism. These findings imply that the concept of the working alliance and specifically the facet Trust deserves more attention in the training of Probation Officers.